Emergency Reasons in Marriage Dispensation (Legal Norms) : A Case Study in Bawean Island, Indonesia - Muhammad Zulfi Al'Ghani; Badrizal Al Hazar; Ease Arent; Muhammad Nur Hidayat; Ramadhani Lausi Mkumbachi (JAMBURA GEO EDUCATION JOURNAL, 2025)
Early marriages in various countries, including Indonesia, can be legalized by the state based on "emergency reasons" in obtaining marriage dispensation in court. The emergency reason pattern can be used as a basis for intervention in handling this case.. This study aims to describe the 'emergency reasons' for marriage dispensation, examine their relationship with the demographic aspects of the offender, and examine the length of time the marriage dispensation was obtained. This research uses a descriptive quantitative survey approach. The instruments used in this research consist of demographic aspects of early marriage actors, as well as a review of "emergency reasons" in marriage dispensation decisions for 157 respondents at the Bawean Religious Court for 2019-2023. This research data analysis uses correlation techniques to show the direction and strength of the relationship between variables. This research proves that there is a relationship between the age and education of early marriage actors and the "emergency reasons" for marriage dispensation decisions, as well as a relationship between the length of the marriage dispensation process and the "emergency reasons" for marriage dispensation decisions. Other results prove that there is no significant relationship between the income of early marriage actors and the "emergency reasons" for marriage dispensation decisions. However, there is a significant correlation with one of the "emergency reasons", namely that the Husband is already working and has an income has a greater chance of getting a marriage dispensation.. The results of this research can be used as important material for regulating marriage dispensations for the Religious Courts, Office of Religious Affairs, Supreme Court of the Republic of Indonesia and other authorities.